BEHAVIOURAL ASPECTS OF INVESTMENT DECISIONS ON FARMS - Magdalena Śmiglak-Krajewska (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2023)
The main purpose of this paper is to identify the behavioral factors that impact the investment decisions made by farm managers. A survey carried out in 2023 with 152farms located in Greater Poland was the source of empirical materials. The study suggests that overconfidence and over-optimism are not widespread in the group surveyed. In assessing their own knowledge of investment topics, 74% of farmers claimed to be equally competent as other agricultural producers. When preparing the implementation of an investment, most respondents (47%) foresee a neutral scenario of how the situation could development, 20% for an optimistic scenario and only13% pick a pessimistic one. Nearly25% of interviewees admitted to rely on the brand’s reputation when choosing a fixed asset (the availability heuristic). The vast majority of farmers surveyed (65%) replied that investing their own funds requires a more in-depth analysis. This corroborates the conclusions made by Richard Thaler and Eric Johnson who discovered that people are less willing to risk their own hard-earned money.